Microtubules offset growth site from the cell centre in fission yeast. - Castagnetti, S; Novák, B; Nurse, P (2007)
The design principles that underlie cellular morphogenetic mechanisms are central to understanding the generation of cell form. We have investigated the constraints governing the formation and positioning of new growth zones in the fission yeast cell and have shown that establishment of a new axis of polarity is independent of microtubules and that in the absence of microtubules a new growth zone is activated near the nucleus in the middle of the cell. Activation of a new growth zone can occur at any stage of the cell cycle as long as the nucleus is a sufficient distance away from previously growing ends. The positioning of growth zones is regulated by the polarity marker Tea1 delivered by microtubules; cells with short microtubules locate the growth zone near the region where the microtubules terminate. We propose a model for the activation of new growth zones comprising a long-range laterally inhibitory component and a self-activating positive local component that is delivered to cell ends by Tea1 and the microtubules. The principle of this symmetry-breaking design may also apply to the morphogenesis of other cells.